Time-dependent three-dimensional simulation of the turbulent flow and heat transfer in czochralski crystal growth including the three-phase boundary movement - Raufeisen, Alexander; Breuer, Michael; Botsch, Tilmann; Delgado, Antonio (High Performance Computing in Science and Engineering 2010 - Transactions of the High Performance Computing Center, Stuttgart, HLRS 2010, 2011)
In the literature, numerical computations of the Czochralski process for crystal growth are conducted using a quasi-steady state assumption for the crystallization neglecting time-dependent effects. In the present work, an algorithm is developed, which allows to calculate the transient behavior of the crystallization interface including the movement of the three-phase boundary and the free surface of the melt. Thus, in conjunction with the computation of the turbulent melt flow and heat transfer, more realistic predictions of the crystal growth can be achieved. Test cases show that with the algorithm, realistic phenomena like crystal diameter increase and decrease during the growth process could be reproduced. © Springer-Verlag Berlin Heidelberg 2011.
UnivIS-Import:2015-04-16:Pub.2011.tech.ITC.stmmec.timede